THE IMPORTANCE OF THE CHEMICAL COMPOSITION OF THE STEM JUICE OF SWEET SORGHUM IN THE PREPARATION OF FEED FOR BEES - M. N Abdurazzokova; N.M.Kurbanov (Research Focus International Scientific Journal, 2024)
This article discusses the topic of the shortage of natural organic food products throughout the world, which is one of the most topical problems of our time, in particular, as a result of the increase in consumer culture of the population, the demand for natural and medicinal food products is increasing, including the growing demand for honey and honey products. In order to provide bee colonies raised in our republic with natural food rich in vitamins and minerals during the off-season period, sugar sorghum was chosen as the object of study, since in our republic the sugar sorghum plant is domesticated, and there is also a sufficient raw material base and conditions for growing. The article also presents methods and results of chemical analysis of processed sugar sorghum stem juice. The amount of vitamins, minerals, carbohydrates, heavy metals, amino acids and proteins contained in the stem juice of sugar sorghum is determined and the information obtained from the results on the beneficial properties intended for creating food for bee colonies is provided. Based on a study of the sugar sorghum plant, it was found that the stem juice is rich in carbohydrates, vitamins, macro- and microelements, and the plant itself produces the expected yield even in arid and saline climatic conditions. When feeding bee colonies in the autumn and early spring months with food prepared by adding condensed sugar sorghum juice, no side effects were observed, and the food was well absorbed by the bees.